PENGARUH KEHARMONISAN WARGA SEKOLAH TERHADAP KUALITAS HASIL BELAJAR PESERTA DIDIK DI SMAN 1 LOHBENER - Didi Sunardi; Dewi Cahyani; Moh. Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of school community harmony on the quality of students’ learning outcomes at SMAN 1 Lohbener. A quantitative descriptive method was used, involving students and teachers as respondents. Data were collected through questionnaires and documentation, then analyzed using statistical techniques to determine the correlation between the variables. The results indicate that a harmonious school environment—characterized by positive relationships among teachers, students, and staff—significantly contributes to improving students’ learning outcomes. The findings highlight that mutual respect, effective communication, and supportive interactions within the school community create a conducive atmosphere for learning. Therefore, maintaining harmony among all school members is crucial for enhancing academic achievement and overall student